Checkout na academia: razões e possibilidades - MOREIRA, Sandra Maria do Nascimento (2014)
In an ever more globalized society, in which people are forced to perform so many tasks at the same time, it is essential for any gym to know the reasons by which their students stop practicing their physical exercises, so that, from the detection of the potential causes, they can adopt actions capable of minimizing this phenomenon. The goal of this study was to identify the dropout reasons of of the systematized physical exercise practicers in a gym at the city of Uberaba/MG. For developing this work, first it was carried out a theoretical investigation about the physical exercise issues, gyms, motivation and adherence. The study comprised 90 people, being 52 females and 38 males, at the age of 18 or more. Subjects were contacted by telephone and invited to participate in a structured interview. Data analysis was done through the Method Content analysis: elaboration technique and signified units analysis, proposed by Moreira, Simões and Porto (2005). Results showed that the issues which caused the subjects to stop doing their exercises at the gym were: Lack of time (44.4%); Distance (20%); Health problems (18.9%); Infrastructure (12.2%) and Not being a member of the gym anymore (8.9%). Findings can help the physical education professional to increase his/her pedagogical practice or contribute to the gym‟s managers to identify and evaluate the points necessary to improve what has been proposed; and still adjust, the best way possible, their products and services in order to meet the demands of the clients and minimize dropouts.